Telomere Length Defines the Cardiomyocyte Differentiation Potency of Mouse Induced Pluripotent Stem Cells. (26th September 2016) - Aguado, Tania; Gutiérrez, Francisco J.; Aix, Esther; Schneider, Ralph P.; Giovinazzo, Giovanna; Blasco, María A.; Flores, Ignacio
Abstract : Induced pluripotent stem cells (iPSCs) can be differentiated in vitro and in vivo to all cardiovascular lineages and are therefore a promising cell source for cardiac regenerative therapy. However, iPSC lines do not all differentiate into cardiomyocytes (CMs) with the same efficiency. Here, we show that telomerase-competent iPSCs with relatively long telomeres and high expression of the shelterin-complex protein TRF1 (iPSC highT ) differentiate sooner and more efficiently into CMs than those with relatively short telomeres and low TRF1 expression (iPSC lowT ). Ascorbic acid, an enhancer of cardiomyocyte differentiation, further increases the cardiomyocyte yield from iPSC highT but does not rescue the cardiomyogenic potential of iPSC lowT . Interestingly, although iPSCs lowT differentiate very poorly to the mesoderm and endoderm lineages, they differentiate very efficiently to the ectoderm lineage, indicating that cell fate can be determined by in vitro selection of iPSCs with different telomere content. Our findings highlight the importance of selecting iPSCs with ample telomere reserves in order to generate high numbers of CMs in a fast, reliable, and efficient way.